Correlated Cashflow Shocks, Asset Prices, and the Term Structure of Equity - Hasler, Michael Nicolas; Khapko, Mariana (Institute for Operations Research and the Management Sciences (INFORMS), 2023)
The term structure of equity risk premium is moderately downward-sloping unconditionally, markedly downward-sloping in good times, and markedly upward-sloping in bad times. An asset-pricing model featuring time-varying correlation between realized and expected cashflow shocks explains these puzzling empirical findings. Indeed, the model- implied slope of the equity term structure is in line with the data, both conditionally and unconditionally, because the estimated cashflow shock correlation is volatile, counter-cyclical, and negative on average. The model also generates realistic asset-pricing moments and a positive relation between the equity risk premium, slope of the equity term structure, and the dividend yield.
Keywords: orrelated cashflow shocks; equity term structure; dividend strips; risk premium; volatility